The Association of Time Budget Pressure and Reduced Audit Quality (RAQ) Behavior (Study among Indonesian Auditors) - Annisa Persiani; Tjiptohadi Tjiptohadi; Sawarjuwono Sawarjuwono (The Indonesian Journal of Accounting Research, 2015)
Abstract: Dysfunctional behaviors such as premature sign-off, reducing the scope of work performed, making superficial reviews, failing to research an accounting principle, failing to obtain sufficient evidence and underreporting of audit time have consistently shown the serious negative consequences in the auditing profession. Some of the previous researches in a similar study suggested that time budget pressure is associated with the occurrence of those behaviors. The objectives of the research are to examine and explain the effect of time budget pressure toward reduced audit quality (RAQ) behaviors among Indonesian auditors.This research is using a quantitative method. A questionnaire is used to collect data. The sample is 78 auditors at 17 Public Accounting Firms in 5 cities in Indonesia. The result indicates that the time budget pressure has a significant influence towards RAQ behaviors. The results suggest that RAQ behavior does occur in Indonesia accounting firms, particularly at staff and senior level. Further questions examined why RAQ practices were used and what areas of the audit were likely to be subject to these practices.Abstract: Perilaku disfungsional seperti sign-off dini, mengurangi lingkup pekerjaan yang dilakukan, membuat ulasan yang dangkal, gagal untuk meneliti prinsip akuntansi, gagal mendapatkan bukti yang cukup dan pelaporan yang tidak tepat waktu audit telah secara konsisten menunjukkan konsekuensi negatif yang serius dalam profesi audit. Beberapa penelitian sebelumnya dalam penelitian serupa menunjukkan bahwa tekanan anggaran waktu dikaitkan dengan terjadinya perilaku tersebut. Tujuan penelitian ini adalah untuk menguji dan menjelaskan pengaruh tekanan anggaran waktu terhadap perilaku kualitas audit (RAQ) yang menurun di kalangan auditor Indonesia. Penelitian ini menggunakan metode kuantitatif. Kuesioner digunakan untuk mengumpulkan data. Sampel adalah 78 auditor di 17 Kantor Akuntan Publik di 5 kota di Indonesia. Hasilnya menunjukkan bahwa tekanan anggaran waktu memiliki pengaruh yang signifikan terhadap perilaku RAQ. Hasilnya menunjukkan bahwa perilaku RAQ terjadi di perusahaan akuntansi Indonesia, khususnya di tingkat staf dan senior. Pertanyaan lebih lanjut meneliti mengapa praktek RAQ digunakan dan bidang audit mana yang kemungkinan akan tunduk pada praktik-praktik ini.